A Habituation Based Islamic Character Learning Management in MI Muhammadiyah 2 Kudus Program Khusus - Dinn, Andhini; Fakhruddin, Fakhruddin; Suminar, Tri (Educational Management, 2019)
The objectives of this study are (1) Describe Islamic character learning planning based on habituation in MI Muhammadiyah 2 Kudus Program Khusus, (2) Describe the implementation of habituation based Islamic learning in MI Muhammadiyah 2 Kudus Program Khusus, and (3) Describe the assessment / evaluation habituation based Islamic character learning in MI Muhammadiyah 2 Kudus Program Khusus.The approach used in this study is a qualitative approach. Data collection techniques used was participatory observation, semitructured interviews, and documentation. The data validity technique that will be used is source, method and time triangulation. The data analysis technique used is based on Miles and Huberman's theory which includes data reduction, data presentation, and verification.The results showed that (1) Planning for habituation programs at MI Muhammadiyah 2 Kudus Program Khusus consisted of several stages including, evaluation, coordination meetings, and program preparation, (2) Implementation of habituation programs at MI Muhammadiyah 2 Kudus Program Khusus were well implemented and orderly, both in the school environment and in the home environment. However, the obstacle is sometimes the lazy attitude of the students, and (3) Evaluation (assessment) of the habituation program at MI Muhammadiyah 2 Kudus Program Khusus is carried out in 2 stages. The first is to use student achievement books for daily assessments at school. The second is using the 2013 curriculum report cards for assessment at the end of each semester.